Pediatric airway: Concepts and management (Research, Society and Development, 2023)
One of the two aspects of greatest relevance in pediatric anesthesiology is the management of the airway (AV). The anatomical differences of this population make it more susceptible to adverse effects of devices designed for its management. Many of the anatomical descriptions at hand are only based on discoveries of more than half a century of descriptions on cadavers. For almost a decade there have been image studies of VA in children that identify the glotte as a more narrow portion, and the larynx more cylindrical than conical. These collateral effects have the impact on selected VA management devices.